2010
DOI: 10.1002/bmc.1377
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COMT isolation by HIC using a dual salt system and low temperature

Abstract: Sodium citrate (SC) and low temperatures between 7 and 5 degrees C are effective in suppressing aggregation of proteins and may be beneficial to be included during a purification process. In this work, we analyzed the application of dual salt system, ammonium sulfate (AS) and SC on binding and elution conditions of recombinant hSCOMT on typical HIC sorbents. Specifically in butyl and octyl supports, the use of, respectively, 300 mM AS/200 mM SC and 25 mM AS/25 mM SC in the loading buffer resulted in complete b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Therefore, we fully refined a HIC workflow, thoroughly screening typical chromatographic parameters: buffer composition, ionic strength, and resin properties (please see Supplementary Materials [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]). Briefly, a wide range of (NH 4 ) 2 SO 4 concentrations in the binding buffer were evaluated as this salt affects the exposure of the hydrophobic moieties of STEAP1, which will further interact with the chromatographic matrices here tested, Butyl- and Octyl-Sepharose, to form a protein-ligand complex [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we fully refined a HIC workflow, thoroughly screening typical chromatographic parameters: buffer composition, ionic strength, and resin properties (please see Supplementary Materials [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]). Briefly, a wide range of (NH 4 ) 2 SO 4 concentrations in the binding buffer were evaluated as this salt affects the exposure of the hydrophobic moieties of STEAP1, which will further interact with the chromatographic matrices here tested, Butyl- and Octyl-Sepharose, to form a protein-ligand complex [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the last decade, several chromatographic approaches have been employed for the purification of SCOMT from complex lysates. In fact, our research group previously reported different strategies for the isolation and purification of SCOMT either by employing hydrophobic resins, an anion‐exchange resin or immobilized amino acids . In fact, the best results were obtained for the two‐step SCOMT purification using a butyl‐sepharose resin followed by a gel filtration step .…”
Section: Introductionmentioning
confidence: 99%
“…Previous stabilization studies carried out for hSCOMT lysates obtained from Escherichia coli showed that DTT and glycerol were effective to stabilize the protein, maintaining its activity [ 28 ]. Moreover, a low concentration of [Ch][DHP] 7.5 mM incorporated in the defined multicompetent buffer (150 mM NaCl, 1 mM MgCl 2 , and 50 mM Tris-Cl, pH 8.0) for a period of 32.4 h at −80 °C has been shown as the ideal conditions to maximize the activity recovery of hMBCOMT [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the most suitable stabilizer buffer for hSCOMTVal108-6His was sodium citrate, presenting a positive T m shift of approximately 10 °C, as well as a good melting temperature curve fit (data not shown). Nevertheless, despite being characterized as a powerful protein stabilizer, sodium citrate is also known to be unable to maintain protein biological activity [ 28 , 45 ]. Therefore, we decided to pursue the studies with the addition of trehalose, cysteine, and glycerol (for the stabilization of hSCOMTVal108-6His lysates) using a Tris buffer base (Buffer A: 10 mM Tris-HCl pH 7.8 and 0.5 M [C4mim]Cl).…”
Section: Resultsmentioning
confidence: 99%